The Influence of Implementing Aqidah Moral Learning on Students' Assertive Behavior - Sya'bana, Alwy; Shohib, Muhammad Wildan; Nubail, Ahamd (AL-WIJDÃN Journal of Islamic Education Studies, 2024)
This study aims to determine whether there is an influence between learning aqidah akhlak on the assertive behavior of students of SMK Muhammadiyah 3 Gemolong Sragen. Learning aqidah akhlak is a set of learning that gives direction or guidance to students by referring to Islamic values and teachings so that students have commendable behavior following Islamic teachings. Assertive behavior is a person's expressing his opinions and feelings without hurting others, including respecting others, being honest, and daring to argue. This type of research is quantitative research with a Regression approach. The population in this study was 85 grade X students of SMK Muhammadiyah 3 Gemolong Sragen. Data collection in this study was by questionnaire method. The data analysis technique uses simple linear regression processed with the help of the SPSS 27 for Windows program. The results showed that (1) Learning aqidah akhlak SMK Muhammadiyah 3 Gemolong Sragen as evidenced by analyzing questionnaires totaling 70 respondents was in the medium category, namely 64.3%. (2) Assertive behavior as evidenced from the test analysis totaling 70 respondents was in the medium category of 70%. (3) There is a significant influence between the learning of aqidah akhlak on the assertive behavior of grade X students at SMK Muhammadiyah 3 Gemolong Sragen with a t-count value of > t table of 3,962 > 0.67811. So that H₁ is accepted, there is a significant influence between the implementation of aqidah akhlak learning on the assertive behavior of students of SMK Muhammadiyah 3 Gemolong Sragen.   Keywords: Education, Aqidah Akhlak Education, Assertive Behavior of Students